2015
DOI: 10.1093/schbul/sbv118
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Myo-Inositol, Choline, and Glutamate Levels in the Associative Striatum of Antipsychotic-Naive Patients With First-Episode Psychosis: A Proton Magnetic Resonance Spectroscopy Study With Implications for Glial Dysfunction

Abstract: Glial disturbances are highly implicated in the pathophysiology of schizophrenia and may be linked with glutamatergic dysregulation. Myo-inositol (mI), a putative marker of glial cells, and choline (Cho), representative of membrane turnover, are both present in larger concentrations within glial cells than in neurons, and their elevation is often interpreted to reflect glial activation. Proton magnetic resonance spectroscopy ((1)H-MRS) allows for the evaluation of mI, Cho, glutamate, glutamate + glutamine (Glx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 87 publications
6
49
0
Order By: Relevance
“…Our hypothesis is further supported by the finding that for the sub-group of patients defined a priori as having residual schizophrenia, the effect size was larger, and indeed was largely responsible for the difference in scores between patients and controls. This finding is consistent with prior evidence indicating increased glutamatergic transmission early in the illness but diminished glutamate in older or more functionally impaired cases [29][30][31][32][33][34][35][36][37]. All three metabolites measured in the ACC were significantly lower in the group with residual schizophrenia than in the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our hypothesis is further supported by the finding that for the sub-group of patients defined a priori as having residual schizophrenia, the effect size was larger, and indeed was largely responsible for the difference in scores between patients and controls. This finding is consistent with prior evidence indicating increased glutamatergic transmission early in the illness but diminished glutamate in older or more functionally impaired cases [29][30][31][32][33][34][35][36][37]. All three metabolites measured in the ACC were significantly lower in the group with residual schizophrenia than in the control group.…”
Section: Discussionsupporting
confidence: 91%
“…These studies provide some evidence of elevated glutamine levels in ACC/mPFC, especially in the early phase of illness. Overall, these studies indicate that glutamate may be unchanged or reduced, especially in more chronic cases, depending on the persistence of symptoms or other factors associated with long-term illness [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Myo-inositol is believed to be an astroglial marker, suggesting an involvement of astrocytes in these findings (Brand et al, 1993;Haroon et al, 2009;Kim et al, 2005;Plitman et al, 2016). Taken together, these data indicate an association between inflammation and glutamate dysregulation in mood disorders including depression.…”
Section: Preclinical and Clinical Studies: Translational Relevancementioning
confidence: 53%
“…(This figure can be found in full colour in the online version of the article.) recent MRS study showed an increase of glutamate in the associative striatum of antipsychotic-na€ ıve patients with first-episode psychosis and found positive correlations between glutamate and myo-inositol (or choline) in the antipsychotic-na€ ıve patients with first-episode psychosis (Plitman et al 2015). Given the role of myoinositol and choline in the glial cells, dysregulation of glial function is likely to result in the disruption of glutamatergic neurotransmission, which may play a role in the psychosis in the first-episode patients.…”
Section: Neuroimagingmentioning
confidence: 99%